A unique porokeratotic variant of inflammatory linear verrucous epidermal nevus - Anup Kumar Tiwary; Dharmendra Kumar Mishra (Wolters Kluwer Medknow Publications, 2017)
Inflammatory linear verrucous epidermal nevus (ILVEN) is a rare variant of nevoid linear inflammatory dermatoses which appear most often in the first 6 months of life and persists for many years or even whole life. Clinically, it often shares many features with linear psoriasis, linear porokeratosis, and other linear dermatoses which can usually be differentiated by an established set of clinical and histopathological criteria. Herein, we are reporting an interesting and rare case fulfilling all the clinical and histopathological criteria of ILVEN in a 13-year-old boy which uniquely revealed cornoid lamella on histopathology so we termed it as "porokeratotic variant of inflammatory linear verrucous epidermal nevus." To the best of our knowledge, only two such cases were reported previously in the literature and none from our country.